2012
DOI: 10.1007/s00540-012-1494-3
|View full text |Cite
|
Sign up to set email alerts
|

Delayed anesthetic preconditioning protects against myocardial infarction via activation of nuclear factor-κB and upregulation of autophagy

Abstract: Delayed APC protected the rat heart from I/R injury. The underlying mechanisms may include NF-κB activation, upregulation of autophagy, and the attenuation of TNF-α, IL-1β, and caspase-3 expressions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 34 publications
3
47
0
1
Order By: Relevance
“…In this study, we also demonstrate that doxorubicin induced cathepsin B expression was accompanied by up-regualtion of NF-κB. Recently, Qiao et al (14) also found a cooccurrence of NF-κB activation and cathepsin B upregulation in delayed anesthetic preconditioning protection against myocardial infarction. Together with the data of the previous studies, our findings suggest that up-regulation of cathepsin B by doxorubicin in cardiomycytes might be associated closely with NF-κB, and the exact mechanisms still deserve further investigation.…”
Section: Resultssupporting
confidence: 81%
“…In this study, we also demonstrate that doxorubicin induced cathepsin B expression was accompanied by up-regualtion of NF-κB. Recently, Qiao et al (14) also found a cooccurrence of NF-κB activation and cathepsin B upregulation in delayed anesthetic preconditioning protection against myocardial infarction. Together with the data of the previous studies, our findings suggest that up-regulation of cathepsin B by doxorubicin in cardiomycytes might be associated closely with NF-κB, and the exact mechanisms still deserve further investigation.…”
Section: Resultssupporting
confidence: 81%
“…It has been reported that delayed sevoflurane preconditioning confers cardioprotection against I/R injury via up-regulation of autophagy prior to ischemia [35] . This result is consistent with those of the present study; SpostC accelerated autophagic flux, characterized by an increase in LC3B-II ( Figure 3B), in sham-operated rats.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiomyocytes death in ischemia-reperfusion injury has been considered to be an accidental cell death resulting from excessive stress which is mainly caused by necrosis. In contrast to this unexpected death, programmed cell death, apoptosis also has been shown to be involved in myocardial ischemia-reperfusion injury [1][2][3]. It is a highly regulated mechanism designed to eliminate cells via caspase activation to maintain homeostasis [4].…”
Section: Introductionmentioning
confidence: 99%